Understanding patients and spouses experiences of patient education following a cardiac event and eliciting attitudes and preferences towards incorporating cardiopulmonary resuscitation training: A qualitative study. (30th January 2018) - Cartledge, Susie; Feldman, Susan; Bray, Janet E.; Stub, Dion; Finn, Judith
Abstract: Aim: The aim of this study was to gain a comprehensive perspective about the experience of patient and spousal education following an acute cardiac event. The second objective was to elicit an understanding of patient and spousal attitudes, preferences and intentions towards future cardiopulmonary resuscitation training. Background: Patients with cardiovascular disease require comprehensive patient and family education to ensure adequate long‐term disease management. As cardiac patients are at risk of future cardiac events, including out‐of‐hospital cardiac arrest, providing cardiopulmonary resuscitation training to patients and family members has long been advocated. Design: We conducted a qualitative study underpinned by phenomenology and the Theory of Planned Behaviour. Methods: Semi‐structured interviews were conducted with cardiac patients and their spouses (N = 12 patient‐spouse pairs) between March 2015–April 2016 purposively sampled from a cardiology ward. Interviews were transcribed verbatim and thematic analysis undertaken. Findings: Nine male and three female patients and their spouses were recruited. Ages ranged from 47‐75 years. Four strongly interrelated themes emerged: the emotional response to the event, information, control and responsibility. There was evidence of positive attitudes and intentions from the TPB towards undertaking cardiopulmonary resuscitation training in the future. Only the eldest patient spouse pair were not interested in undertaking training. Conclusions: Findings suggest cardiac patients and spouses have unmet education needs following an acute cardiac event. Information increased control and decreased negative emotions associated with diagnosis. Participants' preferences were for inclusion of cardiopulmonary resuscitation training in cardiac rehabilitation programs.